Upaya Peningkatan Kualitas Tayangan Sinetron Melalui Focus Group Discussion: Studi Kasus Stasiun TV ANTV - Lina Wati; Afnan Alifiyan; Sri Murdilah Fournawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to evaluate the efforts to enhance the quality of soap operas through the implementation of Focus Group Discussions (FGD) at ANTV, using Sydney W. Head's programming theory as a framework. The research employs a qualitative method, involving observations and analysis of discussion outcomes. The primary focus is on the significance of thorough preparation by ANTV and the selection of appropriate participants as key factors for successful FGDs. The findings indicate that ANTV’s meticulous preparation, including the careful selection of representative participants and effective discussion management, plays a crucial role in obtaining relevant insights into audience preferences. Additionally, the importance of choosing suitable participants is highlighted, as competent participants can provide more valuable and in-depth feedback. The processing of FGD results based on programming theory supports the development of soap operas that better meet audience needs and desires. The study concludes that the success of FGDs is significantly influenced by careful preparation and the selection of appropriate participants. These factors are essential for improving the quality of soap operas at ANTV, and the application of Sydney W. Head's programming theory ensures that FGD insights are effectively implemented to produce engaging and audience-aligned content